PENGEMBANGAN MODUL BERBASIS ETNOSAINS PADA PEMBELAJARAN IPA MATERI GAYA DAN GERAK - Retno Zulya Rahmi; I Nyoman Karma; Nurwahidah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research aims to This research aims to produce products in the form of ethnoscience-based modules in science learning, force and motion materials for class IV SDN 2 Beleka that are valid and practical. The type of research used is development research (R & D) with the ADDIE research model (Analysis, Design, Development, Implementation, Evaluation). The research was conducted at SDN 2 Beleka, Gerung sub-district, West Lombok district, West Nusa Tenggara. The subjects of the study were all 51 grade IV students. The data collection instruments used were material and media validation questionnaires as well as student and teacher response questionnaires. The results of this study showed that ethnoscience-based modules obtained a percentage value of 86.36% by material experts and obtained a percentage value of 88.23% by media experts with very valid categories. In the practicality test by students obtained a percentage value of 92.5% and the practicality test by the teacher obtained a percentage value of 96.9% with very practical categories. Therefore, it can be concluded that based on the results of research, this ethnoscience-based module is very valid and practical to be used in the science learning process of force and motion material in grade IV SDN 2 Beleka.